An improved CS-LS hybrid algorithm on microseismic source location. Issue 1 (1st January 2021) - Da, Shujin; Li, Xuegui; Han, Fei; Li, Hanyang
Abstract : This paper presents a hybrid global optimization algorithm for the localization of microseismic events, which is composed of the Least-Squares (LS) algorithm and the Cuckoo search (CS) algorithm. It significantly reduces the demand for the accuracy of the inversion velocity model. The positioning process is presented as follows: firstly, construct an objective function by utilizing time difference information of P-wave; then, find the final optimal value through iterations by embedding this objective function as the fitness function to the hybrid algorithm. Through simulation experiments, the hybrid algorithm can acquire more accurate locations and a faster convergence speed than the LS algorithm.